Structure of the CoI Intermediate of a Cobalt Pentapyridyl Catalyst for Hydrogen Evolution Revealed by Time‐Resolved X‐ray Spectroscopy. Issue 18 (22nd August 2018) - Smolentsev, Grigory; Soldatov, Mikhail A.; Probst, Benjamin; Bachmann, Cyril; Azzaroli, Nicolo; Alberto, Roger; Nachtegaal, Maarten; van Bokhoven, Jeroen A.
Abstract: Cobalt polypyridyls are highly efficient water‐stable molecular catalysts for hydrogen evolution. The catalytic mechanism explaining their activity is under debate and the main question is the nature of the involvement of pyridyls in the proton transfer: the pentapyridyl ligand, acting as a pentadentate ligand, can provide stability to the catalyst or one of the pyridines can be involved in the proton transfer. Time‐resolved Co K‐edge X‐ray absorption spectroscopy in the microsecond time range indicates that, for the [Co II (aPPy)] catalyst (aPPy=di([2, 2′‐bipyridin]‐6‐yl)(pyridin‐2‐yl)methanol), the pendant pyridine dissociates from the cobalt in the intermediate Co I state. This opens the possibility for pyridinium to act as an intramolecular proton donor. In the resting state, the catalyst returns to the original six‐coordinate high‐spin Co II state with a pentapyridyl and one water molecule coordinating to the metal center. Such a bifunctional role of the polypyridyl ligands can be exploited during further optimization of the catalyst. Abstract : The main question about mechanism of hydrogen evolution by cobalt polypyridyls is the role of pyridyls in the proton transfer: pentapyridyl can act as a pentadentate ligand providing stability to the catalyst or one of the pyridines can effect proton transfer. Time‐resolved Co K‐edge X‐ray absorption spectroscopy indicates that the pendant pyridine dissociates from the cobalt in the intermediate Co I state.